2011
DOI: 10.1007/s00894-011-1282-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the thermostat in the molecular dynamics simulation on the folding of the model protein chignolin

Abstract: Molecular dynamics simulations of the model protein chignolin with explicit solvent were carried out, in order to analyze the influence of the Berendsen thermostat on the evolution and folding of the peptide. The dependence of the peptide behavior on temperature was tested with the commonly employed thermostat scheme consisting of one thermostat for the protein and another for the solvent. The thermostat coupling time of the protein was increased to infinity, when the protein is not in direct contact with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…It has been rigorously shown that the Berendsen thermostat does not generate the true canonical ensemble, with too narrow a distribution of kinetic, potential, and total energies . An incorrect ensemble of energies can lead to systems being trapped in local energy minima, as seen in one study which found the time required for a protein to fold increased with strong Berendsen coupling . In replica exchange molecular dynamics simulations, the Berendsen thermostat has been shown to alter the distribution of folded and unfolded conformations of different peptides at low temperatures. , Kinetic processes which depend on the thermodynamics of the system can be similarly affected.…”
Section: Introductionmentioning
confidence: 99%
“…It has been rigorously shown that the Berendsen thermostat does not generate the true canonical ensemble, with too narrow a distribution of kinetic, potential, and total energies . An incorrect ensemble of energies can lead to systems being trapped in local energy minima, as seen in one study which found the time required for a protein to fold increased with strong Berendsen coupling . In replica exchange molecular dynamics simulations, the Berendsen thermostat has been shown to alter the distribution of folded and unfolded conformations of different peptides at low temperatures. , Kinetic processes which depend on the thermodynamics of the system can be similarly affected.…”
Section: Introductionmentioning
confidence: 99%
“…All simulations were performed using periodic boundary conditions (PBC), all long range electrostatic interactions were calculated using Ewald summation [12] while the SHAKE algorithm was used to fix hydrogen bonds. Integration of atomic motions (2 fs time step) was done using Newtonian equations, while the Berendsen thermostat and barostat algorithms were used in temperature and pressure controls respectively [13].…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the production run was carried out considering an NVT ensemble with Nosè-Hoover thermal coupling. This thermostat (target temperature: 300 K; time constant coupling: 0.2 ps) was applied to the three groups of atoms that build up the system (water, PLGA, curcumin) to avoid any hot solvent-cold solute issue [ 53 ]. Production runs lasted 5 ns to have enough statistics to extrapolate results.…”
Section: Methodsmentioning
confidence: 99%